OPTIMIZATION OF THE DROPPING PERCUSIVE FORCE OF THE MATERIAL IN THE ROLLER OF BALL GRINDING MILL - WANG ShiJiang; ZOU RenPing (Jixie qiangdu)
The theoretical analyses of the ball grinding mill are very necessary for its strength designs and the estimation of its output,but there are a lot of difficulties in the mathematical modeling and theoretical analyses because of the many and complex influence factors. Here,the mechanical principles was used to analyze the percussive force computation problems of the materials in the roller of the ball grinding mill when dropped and collided with the roller,and the function of the percussive force and the dropping angle was given,and the optimization was done with half-division method by a numerical example,the corresponding results of the maximal percussive force and the dropping angle was obtained,The contrast results of the theoretical computations with the product specification parameters supplied by actual ball mill shows that the methods and conclusions in the paper are correct and workable.